Age-related increase of let-7 family microRNA in rat retina and vitreous. (March 2021) - Akamine, Priscilla Sayami; Lima, Cilene Rebouças; Lustoza-Costa, Gabriela Jesus; Fuziwara, Cesar Seigi; Del Debbio, Carolina Beltrame; Kimura, Edna Teruko; Santos, Marinilce Fagundes; Hamassaki, Dânia Emi
Abstract: Vitreous alterations occur from early stages and continue through the normal aging, with gradual lamellae formation and the appearance of liquefied spaces, which eventually leads to complications, such as retinal tear, retinal detachment, and intravitreal hemorrhage. The aim of the present study was to investigate the expression of let-7 miRNA family in the vitreous and retina in newborn (1-3- day-old), young adult (2-month-old), and aging (12-month-old) rats, as well as their role as regulators of vitreous components. MicroRNAs are small, non-coding RNAs that post-transcriptionally regulate gene expression. Our results showed detection of all investigated let-7 isoforms (let-7a, let-7b, let-7c, let-7d, let-7e, let-7f and let-7i) in the retina and vitreous. Although most let-7 members were significantly upregulated in the vitreous during development, only let-7b, let-7c, and let-7e followed this same expression pattern in the retina. Let-7b and -7c increased in aging vitreous as well, and were expressed in vitro by Müller glial cells and their extracellular vesicles. Moreover, let-7 targeted hyaluronan synthase 2 ( Has2 ) mRNA, a synthesizing enzyme of hyaluronan. These observations indicate that let-7 function is important during retina and vitreous development, and that isoforms of let-7 increased with aging, potentially modulating hyaluronan content. Highlights: Let-7 isoforms are upregulated in the aging vitreous. Hyaluronan synthase 2 is a let-7 microRNA validated target in Müller glial cells. Müller glial cells expressed let-7 family microRNA and hyaluronan synthase 2. Let-7 family of microRNAs potentially modulates vitreous hyaluronan with aging.